Metallurgy for the non - metallurgist - Harrison , Donald; Bokrass, Marilyn; ASM International; Lawrence Livermore National Laboratory (Materials Park , Ohio : ASM International, 1987)
A college lecture on metals , starting with basic definitions and the forms of metals and ores , then goes to corrosion and corrosion prevention
tape 1. Metals : a history tape 14. corrasion and corrosion prevention
Copy available in DVD format
Camera, Clarence Watson, Marcia Pollock
Presenter : Robert B. Pond
Keywords: Metallurgy; Metals -- History; Corrosion and anti- corrosives; Ores